Encapsulation of food protein hydrolysates and peptides: a review. Issue 97 (21st October 2015) - Mohan, Aishwarya; Rajendran, Subin R. C. K.; He, Quan Sophia; Bazinet, Laurent; Udenigwe, Chibuike C.
<x xml:space="preserve">Abstract</x> Encapsulation of food protein hydrolysates and peptides using protein, polysaccharide and lipid carriers is needed to enhance their biostability and bioavailability for application as health-promoting functional food ingredients and nutraceuticals.